Longitudinally Extensive Transverse Myelitis: A Sub-Saharan Conundrum. (9th December 2020) - Obayo, Antonina; Mbugua, Sylvia; Ali, Sayed K.
Abstract : Spinal cord schistosomiasis is a rare, underdiagnosed manifestation of schistosomiasis. We present the case of a 36-year-old male who presented to our institution with a one-week history of low back pain with rapidly progressive lower limb weakness, loss of sensation, and flaccid paraparesis. An MRI of the spine showed a longitudinally extensive transverse myelitis from T6 to L1, with enhancement at the cauda equina region. Further review of the images and serological tests eventually led to diagnosis of spinal schistosomiasis. He was treated with praziquantel and high-dose steroids, with minimal improvement in his symptoms.